Research progress of LINE-1 in the diagnosis, prognosis, and treatment of gynecologic tumors - Fu, Jiaojiao; Qin, Tiansheng; Li, Chaoming; Zhu, Jiaojiao; Ding, Yaoyao; Zhou, Meiying; Yang, Qing; Liu, Xiaofeng; Zhou, Juanhong; Chen, Fan (Frontiers in Oncology, 2023)
The retrotransposon known as long interspersed nuclear element-1 (LINE-1), which is currently the sole autonomously mobile transposon in the human genome, can result in insertional mutations, chromosomal rearrangements, and genomic instability. In recent years, numerous studies have shown that LINE-1 is involved in the development of various diseases and also plays an important role in the immune regulation of the organism. The expression of LINE-1 in gynecologic tumors suggests that it is expected to be an independent indicator for early diagnosis and prognosis, and also, as a therapeutic target, LINE-1 is closely associated with gynecologic tumor prognosis. This article discusses the function of LINE-1 in the diagnosis, treatment, and prognosis of ovarian, cervical, and endometrial malignancies, as well as other gynecologic malignancies. It offers fresh perspectives on the early detection of tumors and the creation of novel anti-tumor medications.